Gene Variants and Haplotypes Modifying Transcription Factor Binding Sites in the Human Cyclooxygenase 1 and 2 (PTGS1 and PTGS2) Genes - A.G. Agundez, Jose; L. Gonzalez-Alvarez, David; A. Vega-Rodriguez, Miguel; Botello, Emilia; Garcia-Martin, Elena (Current Drug Metabolism, 2014)
Cyclooxygenases (prostaglandin-endoperoxide synthases, (EC 1.14.99.1) 1 and 2 (COX-1 and COX-2)) are key enzymes with a highly functional and pharmacological relevance. Genetic variations in the corresponding genes PTGS1 and PTGS2 are related to diverse human disorders and adverse drug reactions. Although COX-2 is highly inducible, most genetic association studies have focused on coding region gene variants. The aim of this study is to analyze the genetic variants modifying transcription factor binding sites in human PTGS genes based on the combined use of bioinformatics with 1,000 genomes data and replication by next generation sequencing. Updated information on gene sequences and variants was obtained from the 1,000 genomes website and from a replication sequencing study. Of the 570 upstream PTGS1 gene variants, 43 altered binding sites, either by disrupting existing sequences or by creating new binding sites. The most relevant are the SNP rs72769722, which creates a new binding site for NFKB, and the SNPs rs73559017 and rs76403914, both disrupting binding sites for CDX1. Of the 682 upstream PTGS2 gene variants, 31 altered binding sites, the most relevant being rs689466 and rs20417, which disrupt binding sequences for MYB and E2F, respectively; rs689462 which creates a new binding site for POU3F2; and a haplotype combining the SNPs rs34984585+rs10911904, which creates a new binding site for SRY. This study provides a detailed catalog of variant and invariant transcription factor binding sites for PTGS genes and related haplotypes. This information can be useful to identify potential genetic targets for studies related to COX enzymes.
Keywords: upstream